2015
DOI: 10.1002/phar.1640
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome in Mental Health: Potential Contribution of Gut Microbiota in Disease and Pharmacotherapy Management

Abstract: The gut microbiome is composed of ~10(13) -10(14) microbial cells and viruses that exist in a symbiotic bidirectional communicative relationship with the host. Bacterial functions in the gut have an important role in healthy host metabolic function, and dysbiosis can contribute to the pathology of many medical conditions. Alterations in the relationship between gut microbiota and host have gained some attention in mental health because new evidence supports the association of gut bacteria to cognitive and emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 65 publications
0
19
0
4
Order By: Relevance
“…During the last decade, the human microbiome and the microbiota-gut-brain (MGB)-axis have become a novel epicenter in mental health and specifically stress-related research and have been already acknowledged as a potentially vital new determinant in the field of neuroimmunoregulation, brain development and behavior (219)(220)(221)(222)(223). The MGB-axis represents a bidirectional, key communication pathway between the immune system and the CNS, thus partly mediating the regulation of stress response and early life programming of the neuroimmune system (221,224).…”
Section: Human Microbiome and The Gut-brain-axismentioning
confidence: 99%
“…During the last decade, the human microbiome and the microbiota-gut-brain (MGB)-axis have become a novel epicenter in mental health and specifically stress-related research and have been already acknowledged as a potentially vital new determinant in the field of neuroimmunoregulation, brain development and behavior (219)(220)(221)(222)(223). The MGB-axis represents a bidirectional, key communication pathway between the immune system and the CNS, thus partly mediating the regulation of stress response and early life programming of the neuroimmune system (221,224).…”
Section: Human Microbiome and The Gut-brain-axismentioning
confidence: 99%
“…); appetite control mechanisms [as demonstrated in mice (Lyte et al . )]; disease states such as mental health disorders (Flowers & Ellingrod ) and obesity and its associated metabolic imbalances, including CVD (Arora & Backhed ; Kobyliak et al . ).…”
Section: Resistant Starch and Colonic Healthmentioning
confidence: 99%
“…The influence of gut bacteria and the microbiota on human health is well recognised. Gut bacteria may influence immune function and nutritional acquisition (Sekirov et al 2010); appetite control mechanisms [as demonstrated in mice (Lyte et al 2016)]; disease states such as mental health disorders (Flowers & Ellingrod 2015) and obesity and its associated metabolic imbalances, including CVD (Arora & Backhed 2016;Kobyliak et al 2016). Diet is believed to influence the microbial communities of the gastrointestinal tract (Birt et al 2013) and so the potential of RS to influence gut bacteria is of interest.…”
Section: Influence Of Resistant Starch On Gut Bacteria and The Microbmentioning
confidence: 99%
“…Gut microbiota, the complex microbial communities harbored in the digestive tracts of animals, serve a major role in the host's metabolism (11,12), nutrient absorption or production (13), and immune system (14), greatly contributing to the overall health status of the host (15,16). Accumulating evidence indicated that gut microbiota is closely associated with the incurrence and development of a variety of diseases, including obesity (17,18), diabetes (19) and diarrhea (20).…”
Section: Introductionmentioning
confidence: 99%